2014
DOI: 10.1111/head.12329
|View full text |Cite
|
Sign up to set email alerts
|

Replication of Migraine GWAS Susceptibility Loci in Chinese Han Population

Abstract: Our study confirmed the association of PRDM16 to migraine susceptibility in the Chinese Han population. The results also indicated that replication studies of previous GWAS findings across populations is of importance to validate these associations and to gain a better understanding of migraine susceptibility of potential genetic heterogeneity between populations. Further work is necessary to understand the functional mechanisms underlying these variants identified by GWAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…PRDM16 , which was previously identified as a risk factor for patients with MO in a relatively small‐scale sample, was also suggested to be associated with MO in the present expanded sample size study . Additionally, replication in genetic association studies of PRDM16 rs2651899 has been found in populations from western China, North Indian and Spain . This result further highlights the fact that the pathogenesis of migraine occurs without regard to race.…”
Section: Discussionsupporting
confidence: 81%
“…PRDM16 , which was previously identified as a risk factor for patients with MO in a relatively small‐scale sample, was also suggested to be associated with MO in the present expanded sample size study . Additionally, replication in genetic association studies of PRDM16 rs2651899 has been found in populations from western China, North Indian and Spain . This result further highlights the fact that the pathogenesis of migraine occurs without regard to race.…”
Section: Discussionsupporting
confidence: 81%
“…Finally, Chasman et al described association between SNPs in the PRMD16 , TRPM8 , and LRP1 genes. Recent studies identified association between an SNP in the SLC39A12 gene and the risk for migraine or MWoA in different populations, but failed to find association with SNPs in the GALNT16 gene . In addition, interethnic variability in the associations exists, as LRP1 was found to be associated with the risk for migraine in Indians, but not in Chinese or Swedish individuals …”
Section: Clinical Epidemiological Biochemical Experimental and Phmentioning
confidence: 99%
“…Recent studies identified association between an SNP in the SLC39A12 gene and the risk for migraine 4,5,10 or MWoA 4,11 in different populations, but failed to find association with SNPs in the GALNT16 gene. 4,5,10,11 In addition, interethnic variability in the associations exists, as LRP1 was found to be associated with the risk for migraine in Indians, 4 but not in Chinese 10,11 or Swedish individuals. 5 Regarding genetic studies based on mechanistic hypothesis, histamine seems to be a plausible candidate involve in the etiology or in the clinical presentation of migraine.…”
mentioning
confidence: 99%
“…Interestingly, this connection seems to be present only for individuals of Northern European ancestry [38,39,40,41,42], as studies involving populations from Spain, India, and China found either no association or weak associations between migraine incidence and SNPs near the TRPM8 locus [43,44,45,46,47]. …”
Section: The Role Of Trpm8 In Migrainementioning
confidence: 99%